An application of a novel grey-CODAS method to the selection of hub airport in North Africa - Badi, Ibrahim; Alosta, Abdulaziz; Elmansouri, Omar; Abdulshahed, Ali; Elsharief , Salem (Decision Making: Applications in Management and Engineering, 2023)
Air transportation and airports are indispensable means of the modern world, where well-being and travel time reliability are pillars of strength. In the past few years, passengers traveling into, within, or out of Africa has enormously increased. However, the region lacks the basic facilities for linking African countries to the outside world. The research studies the possibility of assigning the optimal hub airport location in five North African countries, based on five main criteria. The criteria include airport pricing, hard and soft infrastructure, Catchment and landside access, as well as other aspects such as markets and airline partners. The study uses a hybrid grey-CODAS approach to decide the final priority of different decision alternatives. The method was implemented in steps to determine the criteria weights. Four experts participated in the evaluation to determine the importance of each criterion used for the ranking of suggested airport sites. The suggested sites include Cairo airport, Tripoli airport, Tunisia- Carthage airport, Algeria- Houari Boumediene airport, and Morocco- Mohammed V International airport. Model ranking suggested Morocco as the best alternative to locate a hub airport in North Africa.